Effect of diets supplemented with coated plant essential oil on the growth performance, immunity, antioxidant activity, and fecal microbiota of weaned piglets - Niu, Yu; Chen, Yiying; Liu, Jinsong; Liu, Yulan; Xiao, Shiping; Yang, Caimei; Yang, Ting; Huan, Weiwei (Frontiers in Veterinary Science, 2024)
This trial was conducted to compare the effect of diet supplemented with plant essential oil (PEO) and coated plant essential oil (CEO) on growth performance, immunity, antioxidant activity and fecal microbiota of weaned piglets. A total of 360 21-day-old weaned piglets were randomly allocated into 3 groups, including CON, PEO and CEO groups (basal diet supplemented with 0, 500 mg/kg PEO and 500 mg/kg CEO, respectively) for a 4-week feeding trial. The results showed that dietary supplementation with CEO improved average final weight and average daily gain, decreased diarrhea rate, increased antioxidant enzyme activities, enhanced immunoglobulin concentrations, and decreased concentrations of pro-inflammatory cytokines in the serum of weaned piglets (P < 0.05). In addition, CEO addition increased the fecal concentrations of propionic acid and isovaleric acid of piglets (P < 0.05). Spearman correlation analysis showed that fecal microorganisms at the genus level were closely correlated with the volatile fatty acid concentrations. The present study indicated that PEO and CEO could improve growth performance, enhance immunity and increase antioxidant capacity by modulating the microbial flora in weaned piglets. Moreover, the CEO addition seemed to offer positive results improving those of the same PEO alone.